Sites de empresas que comercializam produtos naturais : apropriações possíveis sobre alimentação saudável - Pires, Letícia Corrêa (2014)
The Communication and Health field is the theme of this study. In order to develop the research, the Mundo Verde and Ponto Natural company websites were selected, with the objective to show how these companies relate the suggestions of food consumption in subsections called "Tips" to health and the prevention / treatment of diseases and investigate the congruent and divergent points between the recommendations made by the companies and those described in the Food Guide for the Brazilian Population 2014. Regarding the method, we elected to Depth Hermeneutics, with the methodological procedures of exploratory research, bibliographic and case studies. The analyzes showed the prevalence of suggestions that relate food to weight loss, to prevention / treatment of disease and to nutrients in the texts of the companies.